A Micro-grid connected PV system with MPPT converter - Chow, Zhen Jie. (2013)
This report shall summarise the progress and results from the Final Year Project over a period of 2 semesters, at the School of Electrical and Electronic Engineering. In the previous Final Year Project, a MPPT algorithm was developed in LabVIEW.